Penerapan Teknologi Paper Filigree 3-Dimensi Berbasis Limbah Menjadi Produk Bernilai Ekonomi Tinggi dalam Meningkatkan Pendapatan Rumah Tangga di Talawi Mudik - Olly Norita Tetra; Bustanul Arifin; Hermansyah Aziz; Zulhadjri Zulhadjri; Indrawati Indrawati; Yulizar Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The activity of utilizing waste paper into high economic value products had been carried out in Talawi Mudik. The activity was carried out through the transfer of Paper Filigree 3-Dimensional technology, namely processing waste paper into a classy business based on zero waste. That it can contribute in empowering the community, especially increasing family income, contributing to women who did not work and activated of PKK and dasawisma. The purpose of this activity was to make this technology business opportunity. It can be done by anyone due to the processing in short time, low invest, used tools and materials surrounding. The community service activity started with counseling the dangerous of paper waste in health and environment, followed by training on waste paper processing with simple waste-based techniques. In the training, the participants immediately practiced producing products, assisted until they do themself. The participants were equipped with entrepreneurial concepts and marketing techniques to motivated them to form a home industry. It could impact on new job opportunities, increased family income and the formation of new business groups that provided the program to be sustainable.